Indonesian Gender Justice In School Education - Marthin Steven Lumingkewas; Antonius Missa; Magdalena Indriani Suparlim (RERUM: Journal of Biblical Practice, 2021)
Equality in obtaining education for children, especially girls in rural areas of Indonesia often encounter cultural, religious and ideological barriers from the community.  Educational opportunities are more open to boys than girls for a variety of reasons such as consideration of higher tuition fees, lack of educational facilities and cultural understanding that sees girls as second-grade individuals who can be sacrificed their rights. This subordination of girls is even recorded in a series of education policies that place women as the owners of domestic authority and men to be priests or the backbone of the family. Therefore, in this research using a feminist-sociology approach is expected to provide the results of paradigm changes and perspectives from the government and all elements of society in reviewing the educational curriculum that has so as not to maintain the model gender biased and unfriendly education towards girls' rights in obtaining an education equivalent to that of boys.